Parental modelling in child’s nutrition behaviours and attitudes - Korkmaz, Murat; Yücel, Ali Serdar; Yaman, Çetin; Hergüner, Gülten; Çatıkkaş, Fatih; Kılıç, Bülent (My University, 2015)
While there are many factors influencing obesity, it can be said that the risk of obesity in children is increased by the nutrition behaviours and attitudes of parents as well as negative relationships within the family. In this regard, the aim of this study is to identify obesity and eating habits of children, parents’ attitudes for such behaviours, and factors influencing nutrition. A questionnaire with 4 parts was administrated to the parents of 650 children. Non-parametric and parametric statistical tests were applied on the collected data. At the end of the study, it was found that child nutrition is influenced by psychological and environmental factors, and that the child’s attitudes for healthy nutrition are influenced by the age and gender in children as well as the age, gender, the number of children, and education in parents. Furthermore, it was found that the behaviours of parents that influence the child’s nutrition include especially following the nutrition habits of the child, preventing the child to consume hazardous foods and guiding the child in nutrition.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Eating habits; Health; Nutrition; Parent; Psychology